Analisis Epitope Sel T pada SARS-Cov2 dengan Pendekatan Bioinformatika - Miftahurrahma Rosyda; Faisal Fajri Rahani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
At the beginning of 2020, the world was shocked by the spread of global outbreaks that attacked respiratory like the SARS outbreak in 2003, namely COVID-19. The virus that causes the outbreak called SARS-Cov2. It turns out to have a similarity of ~ 87.5% with SARS-Cov. This similarity can be used to develop drugs and vaccines that are compatible with the current virus. In this case, the bioinformatics approach can be carried out as an initial stage of vaccine development. One way to develop vaccines is epitope-based vaccines. Biological data available and submitted to the public regarding T cell epitopes and protein sequences in viruses can be processed with several bioinformatics tools available online. This study compared the calculation of physicochemical characters between the SARS-Cov epitope and the SARS-Cov2 protein sequence at the same location. The characters being compared are molecular weight, point of isoelectric, aliphatic index, GRAVY, instability index, and antigenicity. Data processing is evaluated by correlation matrix. The results of the processing show that the physicochemical character between SARS-Cov and SARS-Cov2 has a strong relationship.